Rapid identification of heterozygous and homozygous Hemoglobin Constant Spring by SYTO9 with a high resolution melting analysis - Sakorn Pornprasert (2018)
Background: Gel-electrophoresis and ethidium bromide are not ideally suited to large scale analysis in clinical laboratories. Methods: Amplification refractory mutation system-polymerase chain reaction (ARMS-PCR) specific for Hb CS was performed in 10 blood samples from normal individuals and 61 samples containing a peak of Hb CS when analyzed by capillary electrophoresis. Heterozygosity of Hb CS was identified using SYTO9 and high resolution melting (HRM) analysis method. Results: Specific peak heights of amplified fragments of wild type and Hb CS alleles were observed in the heterozygote. Only one peak height of amplified fragments of the wild type allele was observed in the normal individual while only one peak height of amplified fragments of Hb CS allele was observed in the homozygote. HRM analysis interpretation results were completely consistent with the interpretation results from gel-electrophoresis. Conclusions: SYTO9 HRM analysis may be used as an alternative for rapid diagnosis of heterozygosity of Hb CS.